2018
DOI: 10.1111/liv.13959
|View full text |Cite
|
Sign up to set email alerts
|

REtrieval And cure of Chronic Hepatitis C (REACH): Results of micro‐elimination in the Utrecht province

Abstract: To completely eliminate chronic hepatitis C virus (HCV) infection and prevent complications, undiagnosed and also previously diagnosed but lost to follow-up (LFU) HCV patients have to be brought (back) into care for therapy. Retrieval of LFU HCV patients through screening of laboratory diagnostics from the past is feasible and most successful when performed regionally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 14 publications
0
54
0
2
Order By: Relevance
“…Moreover, they should not be considered the target of HCV elimination strategies themselves, but rather a brick in the achievement of HCV eradication in the entire population. Evidence supporting feasibility and effectiveness of micro‐elimination strategies is mounting, both in developed countries and LMICs and in different target populations …”
Section: Eradication and Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they should not be considered the target of HCV elimination strategies themselves, but rather a brick in the achievement of HCV eradication in the entire population. Evidence supporting feasibility and effectiveness of micro‐elimination strategies is mounting, both in developed countries and LMICs and in different target populations …”
Section: Eradication and Eliminationmentioning
confidence: 99%
“…b IFN-based regimens.achievement of HCV eradication in the entire population. Evidence supporting feasibility and effectiveness of micro-elimination strategies is mounting, both in developed countries and LMICs and in different target populations [44][45][46][47][48]. 6 | S PECIAL P OPUL ATIONSTargeting HCV eradication in specific high-risk populations appears to be a highly effective strategy to reduce disease burden.…”
mentioning
confidence: 99%
“…In 2018, the Polaris Observatory reported that only 12 countries were on the track of achieving this result, and Italy is among these . Notably, many countries have already started special programmes to meet this challenge . In this optics, the European Association for the Study of Liver (EASL) International Liver Foundation proposed “micro‐elimination” as a way to eliminate HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the World Health Organization (WHO) 2030 elimination targets [3], focus in the field of HCV healthcare has shifted towards increasing the diagnosis rate, improving linkage to care but also promoting adherence and preventing loss to follow-up [4]. Next to those undiagnosed, patients with HCV who are lost to follow-up (LFU) are an important source of untreated individuals with HCV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Following several small Dutch pilot retrieval projects, the REACH (REtrieval And cure of Chronic Hepatitis C) study aimed to bring LFU patients with HCV back into care, describing that over the past 15 years up to 14% of all individuals with HCV were LFU and eligible for retrieval [5][6][7][8]. The REACH-study achieved the highest retrieval yield with 28% of all local LFU patients with HCV traced but this final turnout was still moderate at most.…”
Section: Introductionmentioning
confidence: 99%